Analisis Sentimen Ulasan Aplikasi MyPertamina pada Google Play Store menggunakan Algoritma NBC - Rihan Maulana; Apriade Voutama; Taufik Ridwan (Jurnal Teknologi Terpadu, 2023)
The MyPertamina application is a digital service application from Pertamina with various services initiated and created to carry out purchases in vehicle fuel transactions. The existence of the MyPertamina application made by PT Pertamina caused reactions and criticism from some application users. Each user has various opinions about the MyPertamina application, as evidenced by the different star ratings in Google Play Store reviews. This study aims to determine the sentiments of MyPertamina application users, which are divided into two classes, namely positive and negative. The dataset in this study uses scraping results from user reviews on the Google Play Store. The data taken to carry out sentiment analysis is from 1 July 2022 to 31 July 2022, and the dataset is taken randomly. The dataset is classified by rating: ratings 4 and 5 as positive sentiment and ratings 1, 2, and 3 as negative sentiment. In this study, Google Colab tools will be used using Python programming. The dataset used is 5722 data labeled positive and negative, with the division of training data by 80% and test data by 20%. The MyPertamina application sentiment analysis results tend to be hostile towards using the application. This study used classification with the Naïve Bayes Classifier (NBC) algorithm. By using the Naïve Bayes Classifier algorithm, it produces 87% accuracy, 86% precision, 90% recall, and 87% f1-score.